Gambaran Protein Urine pada Lansia di Puskesmas Umban Sari Pekanbaru - eli yusrita; Fatma Fatma; Dian Andiani (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Carry on age is someone who has reach age 60 (six twenty) years to on. Along with walking time, a frequent problem faced by the elderly that is happen decline various function from body organs. One of the organs affected changes in the elderly is kidney. Urine as product metabolism pwn content various existing subtances no needed again by the body. Existence still substance useful for body in urine signifies exists error function kidney in work as a filter. One of still substance useful for frequent body there is in urine is protein. Study this aim for know picture of protein in urine in the elderly at the Community Health Center Umban Sari Pekanbaru use method 6% acid. Study this is study descriptive where study done for know description urine protein result with method sour acetate 6%. Based on results study is known that there were 23 respondents (76%) urine protein negative, 5 respondents (17%) urine protein positive (+), and 2 respondents (7%) urine protein positive (++). Conclusion of the research that has been done that amount sample negative more lots than positive.